Pembentukan Organisasi Semi Militer pada Masa Pendudukan Jepang di Indonesia - Sonia R. Matanari; Harry Kriston Situmeang; Rosmaida Sinaga (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
During the Japanese occupation of Indonesia, there was the formation of a semi-military organization which greatly influenced social and political dynamics in the Indonesian region. Semi-military organizations emerged as an instrument of Japanese control to secure colonial interests and also strengthen their domination over the local population and. With its semi-military organized structure, this organization curbed individual freedom and encouraged dependence on the Japanese government. Factors such as violence, intimidation and propaganda were used to maintain Japanese power in Indonesia. In general, this semi-military organization consists of young men aged 17 years and over who are healthy and strong so they can help them in the war. Despite claiming to bring stability and security, this semi-military organization often exacerbated tensions between the local population and the Japanese occupation.